Crude glycerin as an energy feed for dairy cows - Zacaroni, Ozana de Fátima; Souto, Cristielle Nunes (Revista de Ciências Agroveterinárias, 2019)
Crude glycerine is a residue generated from the production of biodiesel. As there was an increase in the demand for biodiesel observed in recent years, there was also a concomitant increase in the production of glycerin, and this by-product is not being used by industries. Thus, new alternatives can be viable, such as the use in dairy cows’ food. The use of glycerin in the animal diet has shown to be a viable alternative to nutritional and economic aspects. Our aim in this review was to demonstrate the use of glycerin in dairy cow diets and the possible effects on its milk production. In several studies it is possible to observe that the crude glycerin can be included in the diet of ruminant animals without causing negative effects on their metabolism, ruminal fermentation and milk production. Studies on the deleterious effects of the inclusion of crude glycerin with high methanol content in the dairy cow diet should be performed.